The Effect of Educational Program on Nurses Knowledge Regarding Physical Assessment of Cardiovascular System in Tertiary Hospital Lahore, Pakistan - Latif, Sobia; Perveen, Kousar; Sarwar, Hajra; Khan, Sadia (Pakistan Journal of Medical & Health Sciences, 2022)
Nurses play as frontline health care provider in clinical setting to assess patient illness, take timely and suitable decision to manage the patient health. In fact, critical care units and intensive care units are critical areas in which nurses frequently work alone, involved in decision making, and manage high risk patients. Literature findings that the physical examination is an important element of patient care in these settings, and nurses are generally well trained to perform a wide range of assessment skills to manage the critical care units. Nursing care has become more and more advance along with complexity of client treatment needed to improve their abilities in doing all physical assessment techniques, which is the first step to providing safe and effective care in clinical setting. Objective: Evaluate the effects of educational interventions on nurse’s knowledge regarding physical assessment of cardiovascular system. Methodology: Quasi experimental study was conducted. Setting: Research data was collected from critical care units in tertiary Hospital Lahore. Study Participants: 36 Nurses were participated in this study. Results: Before educational interventions Critical Care Nurses have minimum level of knowledge regarding physical assessment of cardiovascular system. Finding measured that before intervention less than 50% response of participants n=33 (91.7%) and after intervention above 50 % response of participants n=36 (100%). Study results indicated a significant mean difference between before intervention and after intervention scores of nurses knowledge, t = -29.663, p <0.000, Mean and SD (5.53±1.993 vs. 15.92±1.204). Conclusion: Educational session enable the Critical Care Nurses to incorporate knowledge regarding physical assessment of cardiovascular system into their daily clinical practices. Post-test finding shows highly significant results after workshop, lectures and hands on practice conducted by researcher.